Whey-Gelatin Edible Film: Gelation Time, Solubility and Microstructure with Incorporated Green Tea Powder: Edible Film Whey-Gelatin: Lama Gelasi, Solubilitas dan Mikrostruktur dengan Penggabungan Bubuk Teh Hijau - Fahrullah, Fahrullah; Basriani, Basriani; Anita, Cis; Febryanti, Farah; Fitriyani, Fitriyani (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2025)
Abstract Edible film is a promising eco-friendly alternative to synthetic plastic packaging. This study evaluates the effect of green tea powder on the characteristics of whey-gelatin-based edible films using a completely randomized design with three treatments: P1 (5%), P2 (10%), and P3 (15%), each replicated three times. Results indicate that green tea powder significantly affects gelation time and solubility (P<0.01). Gelation time ranged from 9 minutes 56 seconds to 17 minutes 32 seconds, and solubility ranged from 43.31% to 45.87%. The incorporation of green tea powder altered the microstructure of the films, enhancing surface features and strengthening the polymer matrix. The optimal concentration of green tea powder was 5%, producing the shortest gelation time (9 minutes 56 seconds) and a solubility of 45.87%. These findings highlight the potential of whey-gelatin-based edible films as biodegradable and sustainable packaging for food products, promoting environmental conservation. Abstrak Edible film adalah alternatif ramah lingkungan yang menjanjikan untuk menggantikan bahan kemasan plastik sintetis. Penelitian ini bertujuan mengevaluasi pengaruh bubuk teh hijau terhadap karakteristik edible film berbasis whey-gelatin. Penelitian menggunakan rancangan acak lengkap dengan tiga perlakuan: P1 (5%), P2 (10%), dan P3 (15%), masing-masing dengan tiga ulangan. Hasil menunjukkan penggabungan bubuk teh hijau secara signifikan memengaruhi waktu gelasi dan kelarutan film (P<0,01). Waktu gelasi berkisar antara 9 menit 56 detik hingga 17 menit 32 detik, sementara nilai kelarutan berkisar antara 43,31% hingga 45,87%. Penambahan teh hijau juga memengaruhi mikrostruktur film, memperbaiki fitur permukaan dan memperkuat matriks polimer. Konsentrasi optimal bubuk teh hijau adalah 5%, menghasilkan waktu gelasi lebih singkat (9 menit 56 detik) dengan kelarutan 45,87%. Temuan ini mendukung potensi edible film berbasis whey-gelatin sebagai bahan kemasan ramah lingkungan yang biodegradable.